Front Cover: Photoinitiated Free‐Radical Polymerization of 4, 5, 6, 7‐Tetrahalogenated Fluoresceins (Chem. Asian J. 17/2021). Issue 17 (6th August 2021) - Jae Jung, Young; Nganga, Joseph B.; Cho, Jang‐Hoon; Lee, Hong‐In; Lee, Jungkyu K.
Abstract : The location of heavy halogen atoms (Br and I) in fluorescein derivatives noticeably affected the performance of photoinitiated free‐radical polymerization. We previously demonstrated that 2', 4', 5', 7'‐tetrahalogen fluoresceins (i.e., eosin Y and erythrosine B) increased the polymerization performance in this order: fluorescein < eosin Y < erythrosine B. We, however, observed in this work that a tetrahalogen‐substituted benzoic acid group in fluorescein considerably decreased the performance in this order: fluorescein > 4, 5, 6, 7‐tetrabromofluorescein > 4, 5, 6, 7‐tetraiodofluorescein. More information can be found in the Communication by Hong‐In Lee, Jungkyu K. Lee et al.